(untitled) (Nigerian Journal of Technology, 2025)
The proliferation of counterfeit items has hurt the economic growth, public health, and safety. This work aims to develop an innovative system that can counter and mitigate the threat posed by local and global counterfeiters whose activities have caused untold health and economic hardship to society. This paper proposes a novel blockchain-based anti-counterfeiting system that makes use of a product’s unique characteristics and its geographical location. Prototype system modelling in this study was accomplished using object-oriented software analysis and design techniques, Rapid Unified Process (RUP) and, Rapid Application Development (RAD) methodologies for QR Code and Blockchain applications respectively. Ganache, a private Ethereum blockchain network, was set up to serve as the backend platform. Open-source software such as the Truffe suite and the Solidity compiler were utilised in setting up the Ganache network as well as in compiling and deploying smart contracts written in Solidity. Results proved that the system, when tested on 50 products, shows low energy consumption, high speed of execution at 38.4s on average, QR code scanning time of 9.5ms on average, very high data integrity, and 100% accuracy record when validating whether or not a product is a counterfeit. This work provides a solution for cost-effective and comprehensive anti-counterfeiting measures, featuring key elements such as traceability, immutability, and transparency. The developed system is unparalleled as it combines blockchain technology, unique product inherent features, location information (GPS coordinates), and Track and Trace technologies, to offer a reliable and secure solution to counterfeit trading. This work, therefore, represents a potentially innovative approach to curbing the proliferation of counterfeit products.